What teachers do, observe, and feel in pedagogical practice through the use of digital resources - Flores, Paula Quadros (2017)
In the context of the initial teacher training, namely in the Supervised Pedagogical Practice, it is imperative that the future teacher has the opportunity to develop skills that dignify him in the 21st century, but also that he is encouraged to (re)create the new educational paradigm, finding propulsive impulses of dynamic spheres of innovation and entrepreneurship, responsibility and opportunity for growth. In this sense, and knowing that Information and Communication Technologies (ICT) have an enormous potential for renewal of the educational paradigm and teaching professionalism (Quadros Flores, 2016), the study aims to know educational experiences with ICT: what they do, how they do and what teachers do feel and what impacts do they observe. In this context, we analysed seventeen lesson plans that applied digital resources carried out in the primary school by future teachers attending the Master's Degrees in “Pre-School Education and Teaching of the First Cycle of Basic Education” and Master's Degree in “First Cycle of the Basic Education and Mathematics and Natural Sciences of the Second Cycle of Basic Education”. Three activities were selected with the criterion being innovative, useful, usable and transferable to other contexts. In order to understand what they observe and feel during the implementation of the practices, we opted for a qualitative methodology of a case study. Data were collected from a questionnaire with two open questions applied to seventeen future teachers carrying out the Supervised Educational Practice (internship) in the primary schools. For data analysis, we used content analysis. The results show that, when teachers use technological resources, they adopt a constructivist methodology and that, during the class, they observe impacts on the student, on the learning process and on the school results. The analysis of the answers also reveals effects in three dimensions, essential in the process of teaching and learning: in the motivation, as a means by which the learning is realized, in the understanding that in turn it gives meaning to the learning and the satisfaction, as the result of the motivation that facilitated the comprehension and that, therefore, improves the results of the students and the professional accomplishment of the teacher. When questioned about what they felt in managing an ICT class, they looked at the process of teaching and learning, regarding the student and regarding themselves (teacher). They show, therefore, that the feeling experienced by the teacher in the pedagogical act has a direct relationship with the teacher, as a professional (capacity of methodological, strategic and resource selection, creative capacity in the construction of an environment favourable to the process of teaching to learn), as a person (sensations experienced, responsibility, commitment), but also with the impact on the student. Thus, it is concluded that the success of technology integration depends mainly on the teacher, his technical training in the domain of the tool and his professional training in methodological domain, as well as other skills, such as creativity, resilience, entrepreneurship and leadership.